Kitab "Amtsilati": Dirasah Wasfiyah 'an Thariqah Ta'lim Qawa'idihi bi Ma'had Dar As-Salam Sumani Solok Sumatera Gharbiyah - Baihaqi Anas; Nurlaila Nurlaila (Diwan: Jurnal Bahasa dan Sastra Arab, 2022)
The aim of this research is to find out how to teach the rules and methods of the book 'My Examples' at the Institute of Dar Al-Salam Sumani Solok West Sumatra. In his teaching process since 2016. And the use of this research using the qualitative approach on the case study method. As for the data sources from observation, interview and documents, and to correct the data by triangulating the data sources and discussion. The results of this research are summarized as follows: (1) The method of teaching the rules of Amthalati book at Dar Al Salam Institute is called the Amthalati method. This method is the method in which there are many examples, and the teacher teaches the rules by explaining the examples first and then the rules, and the examples in this teaching come from the Qur’an and the Hadith (2) and that the method of this teaching is by steps means the opening with peace, the Basmalah, the Hazrat, the Fatiha, and repeating the previous education that is more focused on the rules, and the contents are The teacher reads the subject, then orders the students to read the examples in the book, then repeats the examples, then explains the rules, then orders the students to memorize the rules, then gives the students the homework, then concludes with the notes, praise and salutations.